Preclinical pharmacokinetic studies and prediction of human PK profiles for Deg-AZM, a clinical-stage new transgelin agonist - Gu, Xiaoting; Li, Xiaohe; Tian, Weixue; Zheng, Chaoyue; Cai, Yutian; Xu, Xiang; Zhao, Conglu; Liu, Hongting; Sun, Yao; Luo, Zhilin; Zhu, Shuwen; zhou, Honggang; et al. (Frontiers in Pharmacology, 2024)
Deglycosylated azithromycin (Deg-AZM), a newly developed Class I drug with good therapeutic effects on slow transit constipation, is a small molecule Transgelin agonist which has been approved for clinical trials in 2024. The preclinical pharmacokinetic profile of Deg-AZM was investigated to support the further development for Deg-AZM. The results of plasma protein binding suggested that the plasma protein binding rates of Deg-AZM was lower in mice and rats, higher in dogs, and moderate in humans. By investigating the metabolic stability of liver microsome, it was found that the metabolic process of Deg AZM was similar in rat and human liver microsomes. Pharmacokinetic studies conducted on rats or dogs indicated no significant gender difference in the pharmacokinetic behavior of Deg-AZM. In addition, Deg-AZM was rapidly absorbed into the blood and then quickly eliminated from the body. Plasma exposure of Deg-AZM was dose-dependent with no accumulation after continuous gavage administration. Deg-AZM could widely distributed in the tissues without obvious accumulation. Deg-AZM was mainly excreted from the body through the urinary excretion pathway. Furthermore, the pharmacokinetic profiles in human of Deg-AZM at various doses were predicted based on physiologically-based pharmacokinetic (PBPK) models and we found the pharmacokinetic behavior of Deg-AZM showed dose-dependency. These results could provide valuable information to support the first in-human dosage prediction and phase I clinical design.